The Implications of the Nationalist Movement on Inter-ethnic Political Tensions in Eastern Ukraine - Lukuaka, Defrida Suzana; Alexandra, Halomoan Freddy Sitinjak; Saragih, Herlina Juni Risma; Widodo, Pujo (CV. AFDIFAL MAJU BERKAH, 2024)
Ukraine is one of the former Soviet Union states that gained independence in 1991. Ukraine's long history is inextricably linked with conflict, particularly following the Bolshevik invasion of 1921-1922. Under Soviet rule, the Ukrainian people endured considerable suffering across social, economic, and political spheres. One of the darkest chapters in Ukraine's history is the Holodomor. This event ultimately catalysed the Ukrainian independence movement. The Holodomor also engendered an anti-Soviet (Russian) sentiment, as it was regarded as an act of genocide against ethnic Ukrainians. Anti-Russian campaigns intensified following Ukraine's independence and manifested in the Ukrainization movement. However, this movement inadvertently fostered inter-ethnic tensions among Ukrainian citizens, particularly those of Russian ethnicity. The research employs a traditional literature review methodology, involving qualitative data collection and analysis. The conclusion that whilst the Ukrainian Nationalist Movement indeed has implications for political tensions between ethnic Ukrainians and Russians, this is largely attributable to the Ukrainian government's failure to accommodate the aspirations of national minority groups, such as ethnic Russians, in policy-making processes